IMPLEMENTASI RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA RINGAN DI TINGKAT KEPOLISIAN - Dimas Dwi Putro Baharza; Iqbal Tawakal; Ramlin Ahmad (Universitas Kapuas, 2026)
In Indonesia, restorative justice has emerged as a bridge between legal justice and social justice by facilitating dialogue between offenders and victims to reach peaceful resolutions outside formal court processes. This study examines an embezzlement case involving Mrs. Syafrida under the jurisdiction of the South Tangerang Police, which attracted public attention due to humanitarian concerns when her children attempted to sell their kidneys to secure her release. The research employs an empirical juridical method with a qualitative approach, combining legal analysis and field data. Interviews with police investigators were conducted to assess the implementation of restorative justice based on Police Regulation Number 8 of 2021. The findings indicate that restorative justice at the police level contributes to more efficient case resolution, reduces the burden on courts, and helps restore social relations between offenders and victims. This case demonstrates that law enforcement can uphold justice while maintaining humanitarian values and a substantive sense of fairness in resolving criminal cases.